Prevalence and determinants associated with adolescent idiopathic scoliosis: results of screening in Surakarta, Indonesia - Ramadhani, Alinda Nur; Romadhoni, Dea Linia; Awanis, Almas (International Journal of Public Health Science (IJPHS), 2024)
Scoliosis is defined as a vertebral deformity characterized by a lateral deviation of at least 10° with vertebral rotation. Adolescent idiopathic scoliosis is generally found in children aged 10-18 years. Changes in the scoliosis curve are influenced by various etiologic factors including age, sex, growth factors, curve location and biomechanical factors. The study was conducted to determine the prevalence of adolescent iidophatic scoliosis in school students aged 12-15 years in Surakarta city. Physical examination using Adam's forward bending test, scoliometer and risk factor questionnaire. The research subjects were 325 people with an age range of 12-15 years. Research subjects are included in the adolescent idiopathic scoliosis category if the Adam's forward bending test is positive and the scoliometer value is >10°. The highest prevalence of adolescent idiopathic scoliosis was found in school children aged 14 years. The prevalence of adolescent idiopathic scoliosis is higher in female (3.4%) than male students (0.3%). Determining factors that might influence the onset of adolescent idiopathic scoliosis including age, gender, biomechanical factors, habits or lifestyles factors and physical activity.